Educational and careful school function - challenges and threats - Katarzyna Wołk (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The article aims to show the challenges faced by the organization of work in the school common room, but also by educators. The inevitable change is the development of technologies and the possibilities of using them in education. The purpose of the diagnostic survey was to find out the opinion on the image of the teacher - the educator of the school common room and to check what activities are undertaken by the educators to work on this image. The study included 30 tutors of school common rooms in Lublin primary schools. It has been shown that teachers working in school common rooms are divided into those involved in their work and those who perform the minimum of their duties. Educators from the first group are looking for new attractive methods and work tools. The study group showed that they use information technology in their work. Teachers from the second group face many challenges, among others improving your workshop and changing attitude towards the position.